Strategic Market Entry Factors and Market Share Achievement in Japan - Ryans, Adrian B. (Journal of International Business Studies, 1988)
In developing entry marketing strategies for new product markets companies might be advised to target product markets where significant market shares are likely to be achieved. The literature on market share change is reviewed to identify situational and marketing strategy factors associated with market share achievement. Certain hypotheses suggested by this and related literatures were then tested using a database of products introduced into the Japanese market. The results of this analysis indicate that a few key situational and marketing strategy variables account for a large proportion of the variation in achieved market share in Japan.